2022
DOI: 10.1371/journal.ppat.1010389
|View full text |Cite
|
Sign up to set email alerts
|

Blood vessel occlusion by Cryptococcus neoformans is a mechanism for haemorrhagic dissemination of infection

Abstract: Meningitis caused by infectious pathogens is associated with vessel damage and infarct formation, however the physiological cause is often unknown. Cryptococcus neoformans is a human fungal pathogen and causative agent of cryptococcal meningitis, where vascular events are observed in up to 30% of patients, predominantly in severe infection. Therefore, we aimed to investigate how infection may lead to vessel damage and associated pathogen dissemination using a zebrafish model that permitted noninvasive in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…During sterile neuroinflammation, microglia migrate to cerebral blood vessels to regulate BBB integrity but can contribute to barrier breakdown when inflammation is inappropriately sustained (Haruwaka et al, 2019; Yu et al). Loss of BBB integrity has been previously observed during cryptococcal meningitis, which is associated with fungal proliferation within cerebral blood vessels (Gibson et al, 2022). The role of microglia in BBB integrity during cryptococcal meningitis is still unresolved, and we cannot rule out that the reduction in brain fungal burdens observed in our microglia-depleted mice is partially due to effects on BBB integrity caused by depletion of CAMs and/or interruption of inflammatory microglia migration to the blood vessels.…”
Section: Discussionmentioning
confidence: 93%
“…During sterile neuroinflammation, microglia migrate to cerebral blood vessels to regulate BBB integrity but can contribute to barrier breakdown when inflammation is inappropriately sustained (Haruwaka et al, 2019; Yu et al). Loss of BBB integrity has been previously observed during cryptococcal meningitis, which is associated with fungal proliferation within cerebral blood vessels (Gibson et al, 2022). The role of microglia in BBB integrity during cryptococcal meningitis is still unresolved, and we cannot rule out that the reduction in brain fungal burdens observed in our microglia-depleted mice is partially due to effects on BBB integrity caused by depletion of CAMs and/or interruption of inflammatory microglia migration to the blood vessels.…”
Section: Discussionmentioning
confidence: 93%
“…C. neoformans GXM is extensively released and accumulates in the CSF and brain tissue during infection. Recently, it was shown in zebra fish that blood vessel occlusion by this encapsulated fungus is a mechanism for hemorrhagic dissemination of infection (44). Given that GXM is associated with excessive bleeding in the subarachnoid space and increased mortality in mice i.c.…”
Section: Resultsmentioning
confidence: 99%
“…We documented proliferation and accumulation of cryptococci in liquefactive tissue around the border of the brain lesion and considerable deposition of GXM in blood vessels, which may cause compression and occlusion resulting in thrombosis and microinfarctions. In this regard, a recent study on zebra fish demonstrated that cryptococci become trapped in blood vessels, proliferate, cause vascular damage, cortical microinfarctions, and hemorrhage during CME (44). Structural studies on blood vessels and endothelial cells suggest that C. neoformans and possibly GXM cause alterations of tight junction and adhesion proteins impairing cell-cell interactions at the blood-brain barrier interface and vasodilation, which affect the vascular tension and facilitates fungal dissemination (44, 60).…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking claudin-18, a TJ protein highly expressed in airway tissues, exhibited increased susceptibility to C. deneoformans infection through massive multiplication of yeast cells with poor granulomatous responses, reduced production of interferon-γ, and acidification of the alveolar space despite increased presence of immune cells such as CD4 + T cells [37]. In addition, GXM has detrimental effects on endothelial cells associated with blood vessels including alterations of adhesion molecules important for the migration of leukocytes to fight off the infection [38, 39] and vascular vasodilation [40] following cryptococcal infection, which increases vessel tension and promotes fungal dissemination [40].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, GXM localized in blood vessels in brain parenchyma, and its deposition may have serious implications in the maintenance of the host BBB integrity. Vascular GXM accumulation and fungal occlusion have been described as responsible of infarction and hemorrhagic dissemination in CME patients [43, 44] and animal models [40], respectively. Notably, the cortex and hippocampus of GXM-challenged mice were the most affected regions of the brain, suggesting that these animals may also show behavioral and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%